Thoughts on the Use of Space in Polish Cities - Stawasz, Danuta; Masłowski, Patryk (Acta Universitatis Lodziensis. Folia Oeconomica, 2025)
Space is one of the city’s most valuable resources, and its development has a significant impact on the living conditions of residents and the possibilities for creating development processes. The article focuses on identifying trends in the development of space in Polish cities, which began at the turn of the 20th and 21st centuries. The factors and determinants of space development by various city users are discussed. The considerations presented in the article concern issues such as spatial chaos, urban sprawl, the dominance of developers in the housing market, the ghettoisation of urban space, the aesthetics of public places, and the lack of space for public service investments. The effects of the identified trends in the context of rational space management are also presented.